Diversity and Abundance of Benthic Macro Invertebrate at Middle Reaches of Orashi River, Niger Delta - Ngodigha, Sabina Alatari; Hanson, Uyi; Suanu, Deekae, Nanee (MultiTech Publisher, 2024)
Benthic macro-invertebrates are important in any aquatic ecosystem as they serve as bio-indicator of pollution and provide nutrient through their activities. The study was conducted for a period of 12 months from October 2018 to September 2019 along the middle reaches of the Orashi River to investigate the diversity and abundance of Benthic Macroinvertebrate. Samples were collected from each of the sampling stations using Ekman grab. A total of 40,826 benthic macro invertebrates were recorded of three taxa and fourteen species. Highest total number of individuals of 10,644 was in December while the lowest was in September. Species diversity estimated was higher in July and at station 2